How courts impact federal administrative behavior - Hume, Robert J. (Routledge studies in North American politics, 2009)
What impact do federal courts have on the administrative agencies of the federal government? How do agencies react to the decisions of federal courts? This book answers these questions by examining the responses of federal agencies to the U.S. Courts, revealing what happens inside agencies after courts rule against them.